Sulfinyl‐Mediated Stereoselective Functionalization of Acyclic Conjugated Dienes. Issue 20 (18th March 2020) - Colomer, Ignacio; Ureña, Mercedes; Viso, Alma; Fernández de la Pradilla, Roberto
Abstract: The chemo‐ and stereocontrolled functionalization of conjugated sulfinyl dienes in a cascade process that involves a conjugate addition, diastereoselective protonation and a [2, 3]‐sigmatropic rearrangement is reported. Enantioenriched 1, 4‐diol and 1, 4‐aminoalcohol derivatives are obtained in a very straightforward manner. Further functionalization of these structures, including highly stereoselective epoxidation, dihydroxylation and the stereodivergent synthesis of several polyols in a controlled fashion is described. Abstract : Rearrangements : A methodology to prepare acyclic unsaturated 1, 4‐diol derivatives from conjugated sulfinyl dienes has been developed. A cascade process that entails nucleophilic addition to produce a functionalized allylic sulfoxide, followed by [2, 3]‐sigmatropic rearrangement and sulfenate cleavage renders the target molecules with high yields and selectivities (see scheme).